2017
DOI: 10.3892/ol.2017.7353
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of doxorubicin-selected multidrug-resistant human leukemia HL‑60 cells with tolerance to arsenic trioxide and contribution of leukemia stem cells

Abstract: Abstract. The present study selected and characterized a multidrug-resistant HL-60 human acute promyelocytic leukemia cell line, HL-60/RS, by exposure to stepwise incremental doses of doxorubicin. The drug-resistant HL-60/RS cells exhibited 85.68-fold resistance to doxorubicin and were cross-resistant to other chemotherapeutics, including cisplatin, daunorubicin, cytarabine, vincristine and etoposide. The cells over-expressed the transporters P-glycoprotein, multidrug-resistance-related protein 1 and breast-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…demonstrated that As 2 O 3 could be highly effective in the treatment of acute promyelocytic leukemia (APL), and increasing studies have shown that it can induce complete remission, even in patients with relapsed APL, at low doses and with minimal general toxicity [ 8 ]. In other studies, As 2 O 3 has been shown to exert cytotoxic effects on a variety of tumors, such as lung cancer [ 9 ], nasopharyngeal carcinoma [ 10 ], osteosarcoma [ 11 ], neurogliocytoma [ 12 ], hepatoma [ 13 ], cervical cancer [ 14 ], cholangiocarcinoma [ 15 ], breast cancer [ 16 ], gastric cancer [ 17 ] and ovarian cancer [ 18 ]. These effects have been documented in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that As 2 O 3 could be highly effective in the treatment of acute promyelocytic leukemia (APL), and increasing studies have shown that it can induce complete remission, even in patients with relapsed APL, at low doses and with minimal general toxicity [ 8 ]. In other studies, As 2 O 3 has been shown to exert cytotoxic effects on a variety of tumors, such as lung cancer [ 9 ], nasopharyngeal carcinoma [ 10 ], osteosarcoma [ 11 ], neurogliocytoma [ 12 ], hepatoma [ 13 ], cervical cancer [ 14 ], cholangiocarcinoma [ 15 ], breast cancer [ 16 ], gastric cancer [ 17 ] and ovarian cancer [ 18 ]. These effects have been documented in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidence has shown that anti-oxidative signaling was activated in drug resistant cancer cells [30]. For example, the upregulation of antioxidant enzyme catalase resulted in a 10-fold resistance to H2O2 or tert-butyl hydroperoxide in HL-60/AR leukemia cells [31]. Antioxidant enzyme peroxiredoxin II overexpression inhibited cisplatin and H 2 O 2 -induced apoptosis in SNU638 cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our CD20 Ab × mPEG scFv strategy provides an "adaptable" option (clinical mAb × mPEG) for leukemia-resistant treatment as the CD20-end of the BsAb can be replaced by any kind of anti-leukemia tumor marker Ab after CD20 resistance. Another type of drug resistance occurs when leukemia cells express drug resistant proteins, MDR1 and MRP1, which act as drug e ux pumps, which can mediate the doxorubicin resistance [37,38]. The anti-mPEG scFv of BsAbs can actively "grab" any kind of liposomal drug that is modi ed with PEG such as PEGylated polymeric micelles [39], Irinotecan [40] or other PEGylated liposomal drugs in clinical use [41].…”
Section: Discussionmentioning
confidence: 99%